A Step Zero Analysis of the Galapagos Marine Reserve. Issue 5 (3rd September 2017) - Barragan-Paladines, Maria Jose; Chuenpagdee, Ratana
ABSTRACT: Contrary to common perceptions, the creation of protected areas does not start when they are officially declared but generally follows a long process. For instance, the Galapagos Marine Reserve (GMR) was not "born" when it was formally announced on March 18 th 1998, but several decades before that. Through document analysis and key informant interviews, we applied the "step zero" approach to examine what happened prior to the implementation of the GMR. This study reveals that the GMR did not arise from a social and political vacuum; rather, events took place in the distant past, even centuries ago, influenced the reserve's creation and current status. Its establishment was driven by complex geopolitical, economic, social, and environmental factors from both within and outside Galapagos. Additionally, the process of creating the GMR was convoluted, marked by hidden interests and conflictive political agendas that triggered controversies between users. The making of the GMR was also influenced by the interest in promoting "nature-based" tourism, and the regulations that followed had disadvantaged small-scale fishers. This knowledge about the reserve's pre-implementation phase enables a broader understanding of the current challenges facing the performance of the GMR and points to possible governance interventions needed to enhance its sustainability.